Sawn wood yield of Cupressus lusitanica Mill by the tangential sawing system Rendimento em madeira serrada de Cupressus lusitanica Mill por meio do sistema de desdobro tangencial - De Almeida C.C.F.* (2016)
The aim of the study was to evaluate the yield of raw Cupressus lusitanica Mill wood by the tangential sawing process for two diameter classes, from 20 to 27 cm (I) and greater than 27.1 cm (II). The performance evaluation of the sawing process was performed by the determination of yield: gross, with cross-sectional sections with knots, with transverse cutting and trimming of the sections with ground edge,and cross-cutting and trimming of cracked sections and net yield of the process. At the same time, natural and processing defects were quantified. The results showed that Cupressus lusitanica performed well in the tangential sawing process when compared to other species of conifers, and the average net yield was 43.65% for grade I and 45.24% for class II. Overall, the higher diameter class had fewer defects that resulted in lower yield loss than in class I. The arrow archings, even though of little significance, were more evident for the smallest size class. As for the presence of knots and cracks, class I had the greatest number of pieces with defects, size and most expressive knots and cracks along parts of the class II.